Combination strategies to durably suppress HIV-1: Soluble T cell receptors - Zoë Wallace; Praveen K. Singh; Lucy Dorrell (Elsevier, 2022)
Immunotherapeutic interventions to enhance natural HIV-specific CD8+ T cell responses, such as vaccination or adoptive T cell transfer, have been a major focus of HIV cure efforts. However, these approaches have not been effective in overcoming viral immune evasion mechanisms. Soluble T cell receptor (TCR) bispecifics are a new class of 'off-the-shelf' therapeutic designed to address these limitations. These biologics are built on the Immune mobilising monoclonal TCRs against X disease (ImmTAX) platform, which was pioneered in oncology and recently validated by the FDA's approval of tebentafusp for treatment of metastatic uveal melanoma. ImmTAV® are an application of this technology undergoing clinical development for the elimination of chronic viral infections. ImmTAV molecules comprise an affinity-enhanced virus-specific TCR fused to an anti-CD3 effector domain. Engineering of the TCR confers extraordinary specificity and affinity for cognate viral antigen and the anti-CD3 enables retargeting of non-exhausted cytolytic T cells, irrespective of their specificity. These features enable ImmTAV molecules to detect and kill infected cells, even when expressing very low levels of antigen, bypassing ineffective host immune responses. Furthermore, the modularity of the platform allows for engineering of TCRs that effectively target viral variants. In this review, we discuss the progress made in the development of ImmTAV molecules as therapeutics for functional cure of chronic hepatitis B and HIV, from concept to the clinic.